2019
DOI: 10.1590/1413-81232018245.18012017
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference as high blood pressure predictor in school age children

Abstract: Childhood hypertension is becoming more common with the increasing numbers of child obesity, which has encouraged new studies to identify a good anthropometric marker for high blood pressure levels. The objective this study was to identify the best anthropometric predictor of risk of hypertension in children between 8-10 years of age. The Children were evaluated for socioeconomic status and their blood pressure (BP), weight, height, waist circumference (WC) and percentage of body fat (PBF) were measured. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
2
12
0
5
Order By: Relevance
“…These results were similar to some previous studies. A study performed on a Brazilian sample aged 8 to 10 years con rmed that abdominal obesity determined by WC had the closest association with elevated blood pressure, as compared to BMI and percentage of total body fat (PBF) [10]. The risk of hypertension in Mexican children and adolescents were found to be higher in those with increased WC compared to those with high BMI [31].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results were similar to some previous studies. A study performed on a Brazilian sample aged 8 to 10 years con rmed that abdominal obesity determined by WC had the closest association with elevated blood pressure, as compared to BMI and percentage of total body fat (PBF) [10]. The risk of hypertension in Mexican children and adolescents were found to be higher in those with increased WC compared to those with high BMI [31].…”
Section: Discussionmentioning
confidence: 98%
“…WC is commonly used to describe abdominal obesity. Some studies have shown that WC is strongly associated with elevated BP during childhood, as well as other cardiovascular diseases in adulthood [9,10]. WC has, at the least, become one of many indices of metabolic abnormalities among adults.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that an increase of WC in children with a normal weight was associated with an increase in blood pressure [46]. A study by Cruz et al [47] showed that waistline was a good predictor of elevated blood pressure in children aged 8 to 10 years old. This study also found that the WC in hypertensive children was significantly higher than that in non-hypertensive children, and SWC ≥ P 75 significantly increased the risk of hypertension (OR (95% CI): 2.21 (1.13, 4.30).…”
Section: Discussionmentioning
confidence: 99%
“…Different measures of adiposity have been extensively used to predict the risk of cardiometabolic health in both adolescents and adults. Different studies all over the world raise the association of adolescent hypertension with adiposity measures such as higher BMI (Dulskiene et al, 2014; Dutra et al, 2018; Tee et al, 2020) waist circumference (Cruz et al, 2019; Forkert et al, 2016), WHtR (McCarthy & Ashwell, 2006; Moschonis et al, 2018; Rodea‐Montero et al, 2014). In India and other Asian countries too, higher BMI and other adiposity indices are also reported to enhance the cardiometabolic risk (Bharati et al, 2008; Borah et al, 2015; Cheah et al, 2018; Khadilkar et al, 2012; Kotian et al, 2010; Raj, 2012; Sougawa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%